Problematics of Technical Preparation and Constraints in the Spelling System of Madurese Language - Badrudin, Ali; Sofyan, Akhmad (Master Program in Linguistics, Diponegoro University, 2018)
Madura language faces an ironical condition where, as a widely-spoken local language at present, it does not have any standardized spelling which is hardly accepted by linguists of Madurese language. In addition, the spelling problem is a basic way to develop and construct a language. Literally, the spelling of Madura language in 2012 is a revision from the spelling of BM (Bahasa Madura) in 2003 by the users of the language who thought that the language is hard to use. Due to this reason, many observers of Madura language such as writers, men of letters and cultural observers suggested to simplify the use ofMadura language’s symbols. The method that is used in this research is a descriptive qualitative. The data collection is done by in depth interview circumtantially with the observers of Madura language who are specifically experts in three dialects (Sumenep, Pamekasan, and Bangkalan)